CONFLICT RESOLUTION IN FAMILY: JESUS MODEL - Lumingkewas, Edwin Melky (Klabat Theological Review; Vol 3 No 2 (2022): Klabat Theological Review, 2022)
Conflict is something that is integral to humanity. Everybody are facing conflict. Conflict is defined as a social interaction when two or more person or group have a similar desire which is short in supply. There are several types of conflict.  Those types can be include in intra-personal, interpersonal, intra group, and intergroup conflict.  There are five level of conflict.  First, when two person have different perspective, but understand other position and do not have feeling of discomfort. Second is misunderstanding, it is when two person have uncommon understanding about certain situation. Third is when two person see a situation differently and each party feel discomfort at the other. Forth is discord, at this level conflict has reached level where relationship between parties has damaged. And the last is polarization, there is severe negative emotions and behavior with no hope for reconciliation among parties. Keywords: Conflict Resolution, Family.   References Albrecht, G. J., & Albrecht, M. J. (1996). Matthew . The People's Bible (260). Milwaukee, Wis.: Northwestern Pub. House. Bheshtifar, M. & Zare, E. (2013). Interpersonal Conflict: A Substantial Factor to Organizational FailureInternational Journal of Academic Research in Business and Social Sciences May 2013, Vol. 3, No. 5 p. 354-361 Carpenter, M., Bauer, T., & Erdogan, B. (n.d) Principles of Management and Organizational behavior. http://catalog.flatworldknowledge.com/bookhub/reader /2199?e=bauer-ch10_s02 . Retrieved September 2014 Donais, B (2006) http://www.mediate.com/articles/donaisB2.cfm Retrieved, 5 September 2014 Anderson, D. (2012). The Role of the Family , http://www.payh.org/the-role-of-the-family/    retrieved 3.2. 15 Evans, A. T. (2000). The best is yet to come: Bible prophecies through the ages . Includes indexes. (58). Chicago: Moody Press. Gardner, R. B. (1991). Matthew . Believers church Bible commentary (53). Scottdale, Pa.: Herald Press. Gelfan, M. J., Robert D. Pritcharrd (ed.) (2008). The Psychology of Conflict and Conflict Management in Organizations , New York: NY: Taylor & Francis. Naarm (2014). http://www.naarm.ernet.in/virtual/conflict_management1.htm, retrieved, 13 July 2014 http://www.prosci.com/change-management/definition/   Retrieved September 9 th 2014 Jeong, H. W. (2010), Conflict Management and Resolution: An introduction , Oxon: UK, Routledge.  Kinnander, M. (2011), Conflict Management: How to Manage Functional Conflicts within Project Teams , Gothenburg Sweden. Chalmer University of technology p.4 Rahim, M. A. (2001), Managing Conflict in Organization , Westport, CT. Quorum Books. Runde, E. R. & Flanagan, T. A. (2008), Building Conflict Competent Teams , San Francisco, CA: John Wiley & Sons Straks, J. (2006). Reduce Stress and Improve Outcomes: A Conflict Management Primer for Business Leaders .  http://www.mediate.com/articles/straksJ1.cfm   Retrieved September 2014. White, E. G. (1898; 2002). The Desire of Ages; Conflict of the Ages Series , Vol. 3; Washington, DC: Pacific Press. Whyte, A. (2011). Bible Characters - The New Testament . Joseph Kreifels. Publisher: London: Oliphant, Anderson & Ferrier (April 2011) Publication Date: 1896 Wiersbe, W. W. (1996, c1989). The Bible exposition commentary . "An exposition of the New Testament comprising the entire 'BE' series"--Jkt. (Mt 4:1). Wheaton, Ill.: Victor Books. Saadia Dildar, Aisha Sitwat, and Sumaira Yasin (2013). Intimate Enemies: Marital Conflicts and Conflict Resolution Styles in Dissatisfied Married Couples. Middle-East Journal of Scientific Research 15 (10).   Idosi Publication. DOI 10.5829/idosii.mejsr.2013.15.10.11581. p. 1433-1439 http://www.healthychildren.org/English/family-life/family-dynamics/Pages/Roles-Within-the-Family.aspx American Academy Pediatrics (2014). Roles within the Family . http://www.healthychildren.org/English/family-life/family-dynamics/Pages /Roles-Within-the-Family.aspx